PEACE GENERATION: Education to Create Peace and Tolerance for Junior High School Students at Unismuh Makassar - Hafid, Hilda; Hijrah, Hijrah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Indonesia's diversity in ethnicity, race, religion, language, and values often leads to conflict. Social tensions rooted in group-based violence that sporadically erupt in various regions of the country highlight the fragility of the sense of unity within the Indonesian nation-state. This diversity, if well-managed, can be a blessing. However, if neglected, it can become the seed of disaster. Peace Generation Camp is an activity carried out with students of SMP Unismuh Makassar. It is one of the efforts aimed at instilling tolerance, celebrating differences, and encouraging critical thinking. The program is structured around four core themes delivered in separate sessions: God, Why Am I Different?, Blessings in Diversity, Effective Communication and Practicing Peace in Daily Life. The implementation of the program is supported by a team of student volunteers from Unismuh who serve as facilitators in group discussions and games. Through this program, students are expected to learn how to appreciate differences and become more open to diversity within their school and broader social environment.